Geomorfologia e os estudos planetários: o uso das imagens hirise e os processos eólicos na cratera Herschel, Marte - Santos, Diego Dal Pozzolo dos (2021)
The Aeolian processes are key elements to understand the surfaces of celestial bodies with atmosphere. This paper performs an analysis of aeolian activity on Herschel crater, from two dune fields in different topographical settings. At East field, between small simple craters, and at West, the dune field is located inside a large impact crater near to uplifted central peak. As source of data will be employed high resolution images (spatial resolution 0,25 m/pixel) and digital terrain models (DTM), with 1m / pixel spatial resolution, generated by HiRISE sensor of orbital probe Mars Reconnaissance Orbiter (MRO) and Mars Climate Database (MCD) meteorological database data of direction and wind speed. Were measured horizontal parameters (Area,Azimuth length, width , and length/width ratio) and vertical parameters (height of crest (Hc), height of slipface (Hs),slipface slope, curvature)of 10 dunes in each field. Altimetry, slope and slope orientation maps of both fields were aslo prepared using the ENVI and QGIS softwares.The results indicates Herschel East dunes are fat,free, and in uphill. The taller and steepest dunes are located at side of impact craters, due to horseshoe vortex effect It is characterized by the unimodal wind regime in the predominant N-S axis, wind patterns of the Tsoar type at night and Bagnold during the day. It has little azimuth variation. Predominance of the slope between 5-10º. There is a predominance of NW, E, W (Windward) SE, (slip) orientations. Similar conditions have been identified in similar terrestrial environments such as, White Sands, (New Mexico), Wolfe Creek, (Australia) and Lagoa da Conceição (Santa Catarina).The dunes from Herschel West are slim, in downhill, some anchored by Yardangs. It presents acute bimodal wind patterns on the predominant axis W-E, Bagnold type wind pattern at night and Tsoar during the day. Predominance of orientations E, SE, NE (windward), W, NW (landslide). A lot of azimuth variation. Predominance of the 5-10º slope. As a terrestrial analogue, we have the Liwa Oasis (United Arab Emirates / Saudi Arabia).